2019
DOI: 10.1371/journal.pone.0222572
|View full text |Cite
|
Sign up to set email alerts
|

The impact of peer pressure on cigarette smoking among high school and university students in Ethiopia: A systemic review and meta-analysis

Abstract: BackgroundCigarettes and their by-products (i.e., smoke; ash) are a complex, dynamic, and reactive mixture of around 5,000 chemicals. Cigarette smoking potentially harms nearly every organ of the human body, causes innumerable diseases, and impacts the health of smokers and those interacting with the smokers. Smoking brings greater health problems in the long-term like increased risk of stroke and brain damage. For students, peer pressure is one of the key factors contributing to cigarette smoking. Therefore, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
28
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 32 publications
4
28
0
1
Order By: Relevance
“…[ 1 12 ] Therefore, youth who receive accurate information about alcohol- or smoking-related health effects might have increased health awareness and know-how to deal with the risk of using substances. [ 7 14 27 ] However, vice versa , they receive inaccurate information, especially from parents or peers who drink or smoke, such as positive outcomes of alcohol use or smoking and share social network norms toward substance used;[ 13 14 28 ] youth may trust their parents or peers easily and are unable to interpret and judge the relevance of the information on risk factors. This, in turn, lead them to make decisions of trying drinking alcohol or smoking.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 1 12 ] Therefore, youth who receive accurate information about alcohol- or smoking-related health effects might have increased health awareness and know-how to deal with the risk of using substances. [ 7 14 27 ] However, vice versa , they receive inaccurate information, especially from parents or peers who drink or smoke, such as positive outcomes of alcohol use or smoking and share social network norms toward substance used;[ 13 14 28 ] youth may trust their parents or peers easily and are unable to interpret and judge the relevance of the information on risk factors. This, in turn, lead them to make decisions of trying drinking alcohol or smoking.…”
Section: Discussionmentioning
confidence: 99%
“…[ 1 5 12 ] Moreover, prior researches have shown that HL determinants such as age, gender, household income, alcohol expectancies (AEs), and smoking outcome expectancies (SOE). [ 5 13 14 15 16 17 ] Nevertheless, HLSU may influence the substance abuse, but there is no other study related among adolescent and there are no statistics and evidence available on this subject in Thailand. [ 18 19 ] Thus, investigating the effect of HLSU on substance abuse may help reduce the risk of their substance abuse behaviors and provide guidance for developing the substance abuse prevention interventions.…”
Section: Introductionmentioning
confidence: 99%
“…The quality of each study was assessed using the following criteria: representativeness of the study, adequate sample size, acceptable non-response rate, used validated measurement tool, comparability of the study, description of outcome assessment, and used appropriate statistical tests. Articles with a global rating score ≥ seven out of 10 were considered to be high quality [15,16] (Supplementary file 3).…”
Section: Data Extraction Process and Quality Assessmentmentioning
confidence: 99%
“…Overall, studies with a quality score of ≥ seven were considered as highquality. Lastly, all the 21 included articles were categorized as high-quality studies [15,16].…”
Section: Characteristics Of Eligible Studiesmentioning
confidence: 99%
“…The transition from high school to college is very challenging for most fresh students. Because of difficulties in adjusting to the new environment and forming new social relationships, and being separated from close relationships, university students are more likely to feel lonely and depressed in their first academic year (Leshargie et al, 2019;Karadogan et al, 2018;Zhang et al, 2020). Azagba et al (2020) revealed the findings of a study on students in the United States from 2011 to 2018, according to which current young cigarette smokers smoked on fewer days and fewer cigarettes per day, and the age of the first use of cigarettes increased.…”
Section: • 1 Introduction and Theoretical Backgroundmentioning
confidence: 99%